SIKAP PETANI PADI TERHADAP BENIH UNGGUL PADI BERSERTIFIKAT DI KECAMATAN KARANGPANDAN, KABUPATEN KARANGANYAR - Nurul Fajri Mayalibit; Suwarto Suwarto; Eksa Rusdiyana; Arip Wijianto (Universitas Sebelas Maret, 2017)
This research to analyze the attitude of farmers against rice seed certified, analyze the factors forming attitudes, analyze the relationships between the factors forming the attitude with the attitude of farmers, as well as analyzing the difference in the attitude of farmers. This study determined the location intentionally (purposive) in Karangpandan Subdistrict, Karanganyar District. Using multi-stage random cluster sampling. The data are classified using the width of the interval. To find out the relationship between the factors forming the attitude with the attitude of farmers rice against the rice seed certified used Spearman Rank correlation test (rs). To know the difference in the attitude of farmers used Wilcoxon test using a computer program SPSS 16.0 for windows. The results showed that the respondent's age category high, formal education category low, personal experience category medium, the influence of other people considered important category very high, and the influence of the mass media categories medium. The attitude of farmers against Seed Certified Padi 56.67%, farmers very agree rice certified seed. Rank Spearman correlation test based on 95% confidence level indicates that the relationship was not significant between age and the influence of mass media with the attitude of farmers rice against the rice seed certified. The significant relationship between formal education with the attitude of farmers rice against the rice seed certified. While personal experience has a very significant relationship but in the opposite direction and influence others who are considered essential to have a very significant relationship in one direction with the attitude of farmers against rice seed certified.